Unveiling Ethical Horizons: A Contemporary Analysis of MBA Students' Perceptions on Business Ethics in Nepal - Khanal, Krishna; Prajapati, Bikram (Scientific Researches in Academia, 2023)
Students are our future generation who are going to have substantial role in Nepal’s business and economy. The basic objective of this study is to understand where MBA students stand on ethical issues. This study was motivated by a need to understand the students better so that we can design our courses on business ethics more efficiently. We compare perceptions among groups of students based on their gender, work experience, age, prior exposure to ethics education and MBA specialization. A survey consisting of 10 small ethical situations were completed by 164 MBA students. The results show that in general MBA students have good perception on Business ethics. The results further indicate that there is no difference in ethical judgement related to gender. The age factor and work experience does not necessarily have a significant impact on ethical awareness. Also, at the same time, there is no evidence to suggest that the MBA major (specialization) and prior ethics education impact significantly on ethical judgement.